Hydrogen embrittlement behavior of SUS301L-MT stainless steel laser-arc hybrid welded joint localized zones. (March 2020) - Fu, Z.H.; Yang, B.J.; Shan, M.L.; Li, T.; Zhu, Z.Y.; Ma, C.P.; Zhang, X.; Gou, G.Q.; Wang, Z.R.; Gao, W.
Highlights: HE behavior of localized zones in SUS301L-MT stainless steel was investigated using SSRT tests during in situ electrochemical hydrogen charging. HE cracks in BM and HAZ specimens initiated along αˊ/γ interface near the specimen edge. HE cracks in WM specimen initiated along the δ-ferrites distributed at austenitic grain boundaries. HE cracks propagated in BM, HAZ and WM exhibited hydrogen enhanced local plastic deformation and hydrogen induced decohesion mechanisms controlled by the hydrogen diffusion behavior in the front of cracks tips. Abstract: Hydrogen induced stress corrosion cracking behavior of SUS301L-MT laser-arc hybrid welded (LAHW) joints has been investigated in our previous works. However, the hydrogen embrittlement (HE) behavior in each zone of this joint is still unclear. In this work, in combination with microstructures, cracks propagation paths and fracture surface morphologies analysis, in situ electrochemical hydrogen charging during slow strain rate tensile (SSRT) tests were performed on the specimens cut from base metal (BM), heat-affected zone (HAZ) and weld metal (WM) in SUS301L-MT stainless steel LAHW joints to investigate the HE behavior of each zone. The results indicated that deformation induced martensite transformation occurred in BM and HAZ specimens during SSRT tests, resulted in cleavage morphologies on the fracture center and dimples on other areas. The fracture surface of WM specimen was all covered with dimples. During in situ hydrogen charging, the cracks in BM and HAZ specimens initiated along α ˊ/ γ interface near the specimen edge. The cracks in WM specimen initiated along the δ -ferrites distributed at austenitic grain boundaries. After the cracks initiated, the hydrogen concentration distribution in combination with stress field at the front of cracks tips would induce the cracks propagation by "hydrogen enhanced local plastic deformation" and "hydrogen enhanced decohesion" mechanisms. As a result, mainly fracture characterizations of intergranular cracking, transgranular cleavage and secondary cracks formed on the fracture surface.